The Place of Person’s Freedom in Globalized Social-Political Model of the Crisis Epoch - Shioshvali, Irma (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
The modern world is characterized with sharply identified crisis signs. In such social- political life person’s freedom issue gains new measurement, but because of its universal importance it still preserves the function of the highest criteria of progress. The article discusses the modern problems of the personal freedoms in the era of transformations in the basis of social philosophy